The Instruction Model Based on Cooperative Learning and Game-Based Learning for Enhancing English Communication Abilities - Juthamaneepong, Sirinrada; Sriarunrasmee, Jaemjan; Chuacha, Sumalee (Arts of Management Journal, 2023)
The purposes of this research were as follows: 1) to study the current situation, problems, and needs of English language teaching and learning in order to promote English language communication. 2) to develop an instruction model based on cooperative game-based learning using board games and 3) and examine the effects of an instruction model based on cooperative game-based learning using board games approach on English language communication skills. The sample group used in this research consists of 30 students from Grade 11 at Ubolratana Rajakanya Ratchawittayalai Nakhonratchasima School during the second semester of the academic year 2022. They were selected by purposeful sampling. The research utilized teaching plans based on collaborative learning and game-based teaching approaches, board games as learning media, and assessments of speaking and listening abilities in English. The research findings indicate that an instruction model based on cooperative game-based learning using a boardgame teaching approach consists of three stages: 1) construction of knowledge; 2) socialization; and 3) evaluation. The approach comprises seven important components: 1) learning environment; 2) learners; 3) teachers; 4) communication; 5) content; 6) board game media; and 7) assessment. The evaluation results by experts show that the approach aligns with cooperative and game-based learning and is consistent with Grade 11 students. The index of conformity ranges from 0.6 to 1.0. Furthermore, the student’s English language communication abilities at the Grade 11 level were statistically significantly higher after using the approach at a significance level of.05.